(untitled) - Patnaik, Pradyot (New York, 2004)
This comprehensive, up-to-date reference offers chemists and chemical engineers detailed coverage of the full range of analytical methods, including all conventional wet and instrumental techniques. It also provides information on the preliminary operations of analysis, preliminary separation methods, quality control and quality assurance, and statistics in chemical analysis.
Các phương pháp phân tích hóa học hiện đại
Keywords: Chemistry, analytic; Handbooks, manuals, etc